2012
DOI: 10.1111/sjop.12004
|View full text |Cite
|
Sign up to set email alerts
|

Goals influence memory and imitation for dynamic human action in 36‐month‐old children

Abstract: Adults’ memory for action is organized according to a hierarchy of goals. Little previous research has examined whether goals also play a crucial role young children’s memory for action, and particularly whether goal information is privileged over veridical sequential order information. The current experiment investigated 3-year-old children’s (N = 40) memory for naturally occurring interleaved action sequences: Sequences in which an actor switched back and forth between carrying out actions related to two dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 63 publications
1
26
2
1
Order By: Relevance
“…The results of Experiment 2 suggest that an important aspect of early episodic future thinking development is the understanding that past knowledge can be useful to help address future problems and goals. This connection becomes particularly important given recent literature that has underscored the role of goal structure in organizing event representations and guiding event memory in early childhood (Bekkering, Wohlschlager, & Gattis, 2000;Gleissner, Bekkering, & Meltzoff, 2000;Loucks & Meltzoff, 2013;Loucks et al, 2017;Williamson & Markman, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The results of Experiment 2 suggest that an important aspect of early episodic future thinking development is the understanding that past knowledge can be useful to help address future problems and goals. This connection becomes particularly important given recent literature that has underscored the role of goal structure in organizing event representations and guiding event memory in early childhood (Bekkering, Wohlschlager, & Gattis, 2000;Gleissner, Bekkering, & Meltzoff, 2000;Loucks & Meltzoff, 2013;Loucks et al, 2017;Williamson & Markman, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Once infants map labels to such sequences, they will need to extend them to new contexts in order to use language generatively (e.g., the action sequence of bath time can be labeled as such whether dad or the babysitter performs it). Finally, how does the presence of other cues, like intentions (Baldwin et al, 2001), familiarity (Hespos, Saylor & Grossman, 2009), or goals (Loucks & Meltzoff, 2013), influence the role of sequential predictability in event segmentation? In natural language processing, word segmentation is facilitated by the conjunction of multiple cues, such as sequential predictability, familiar words, and isolated utterances (Mersad & Nazzi, 2012; Lew-Williams, Pelucchi, & Saffran, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research with adults suggests that event memory is functionally dependent on how the event was segmented (Flores et al, ; Sargent et al, ; Swallow et al, ; Zacks et al, ), and research with children provides further insights into how memory preserves event structure that is created during event segmentation. Imitation research reveals that 3‐year‐olds’ memories for observed action events, both familiar and novel, are organized based on hierarchical goal structure rather than the temporal order in which the actions were observed (Loucks & Meltzoff, ; Loucks, Mutschler, & Meltzoff, ), suggesting children segment events according to goal hierarchies and preserve this segmentation in their memory for the events.…”
Section: Significance Of Event Segmentation For Other Developmental Pmentioning
confidence: 99%